Seroprevalence and pathological investigation of salmonellosis in poultry - M. Al Mamun; M. Jamal Uddin Bhuiyan; M. Ali Zinnah; Abul Khair; M. Mahmudul Hassan; M. Bashir Uddin (Eurasian Journal of Veterinary Sciences)
Aim: Aim of this study was to determine the seroprevalence of Salmonella along with pathological investigation in poultry. Materials and Methods: A total of 200 birds were selected randomly for collection of serum for serum plate agglutination test and 28 samples were collected from suspected birds for gross and histopathological study. Serum plate agglutination test was performed for detection of seroprevalence and routine histopathological method was used. Results: Out of 200 samples, 76 birds were Salmonellapositive giving the overall seroprevalence of 38.0%. Various macroscopically and microscopically pathologic lesions observed especially in the liver (haemorrhage, necrotic foci, heterophil infiltration) and intestine (goblet cell proliferation). Conclusion: Further studies are need for the determination of the presence of Salmonella infection in farms of Bangladesh.